2008
DOI: 10.1542/peds.2007-2820
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Height in Adolescent Girls With Anorexia Nervosa

Abstract: Our data suggest that preservation of height potential in this cohort of girls with anorexia nervosa may be a consequence of delayed bone age. Hypogonadism may negate the deleterious effects of undernutrition on stature by allowing for a longer duration of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Reports have indicated lower than expected, normal and even higher than expected stature in girls with AN compared with genetic potential or controls [6365]. Similarly, both height deficits and height within range of genetic potential have been reported in boys with AN [7, 66].…”
Section: Statural Growthmentioning
confidence: 96%
See 1 more Smart Citation
“…Reports have indicated lower than expected, normal and even higher than expected stature in girls with AN compared with genetic potential or controls [6365]. Similarly, both height deficits and height within range of genetic potential have been reported in boys with AN [7, 66].…”
Section: Statural Growthmentioning
confidence: 96%
“…In contrast, later onset of AN (when growth is almost complete) would not be expected to cause significant statural deficits. Studies that have reported no change in height potential or height SDS in AN suggest that a delay in bone age associated with high GH concentrations (and direct GH effects on the growth plate) may cause a sparing of height deficits in adolescents with AN, particularly when the disease is not very severe [63]. …”
Section: Statural Growthmentioning
confidence: 99%
“…Low levels of IGF1 might be an adaptive response to preserve energy by decreasing expenditures on growth in states of chronic starvation 33 . GH resistance negatively affects longitudinal bone growth in adolescent boys with anorexia nervosa 34 , but data are conflicting in adolescent girls with anorexia nervosa 35,36 . Elevated GH levels might also have a protective role by maintaining euglycaemia via gluconeogenesis 37 and mobilizing fat stores via lipolysis 38 in states of chronic starvation.…”
Section: Hypothalamic–pituitary Dysfunctionmentioning
confidence: 99%
“…Additionally, suboptimal energy intake (for maximum weight gain) reduces peak bone mass in growing rodents [2, 5] and minipigs [30]. In girls, anorexia nervosa slows bone growth but need not drastically reduce adult stature because epiphyseal closure is delayed and bone growth continues, albeit at a slower rate and for a longer interval of time [31]. Increasing energy availability following energy deprivation results in at least partial growth recovery [32, 33].…”
Section: Discussionmentioning
confidence: 99%